Mesenchymal Stem Cells for the Treatment of Idiopathic Pulmonary Fibrosis - Argyrios Tzouvelekis (Frontiers in Medicine, 2018)
Idiopathic pulmonary fibrosis (IPF) is an inexorably progressive lung disease of unknown origin. Prognosis is poor, with limited treatment options available, and the median survival remains just 3–5 years. Despite the use of pirfenidone and nintedanib for the treatment of IPF, curative therapies remain elusive and mortality remains high. Regenerative medicine and the use of cell-based therapies has recently emerged as a potential option for various diseases. Promising results of preclinical studies using mesenchymal stem cells (MSCs) suggest that they may represent a potential therapeutic option for the treatment of chronic lung diseases including IPF. Encouraging results of Phase 1 studies of MSCs various have reduced safety concerns. Nonetheless, there is still a pressing need for exploratory biomarkers and interval end-points in the context of MSCs investigation. This review intends to summarize the current state of knowledge for stem cells in the experimental and clinical setting of IPF, present important safety and efficacy issues, highlight future challenges and address the need for large, multicenter clinical trials coupled with realistic end-points, including biomarkers, to assess treatment efficacy.